The nation under scrutiny: A post-colonial critique of selected editorial cartoons in Isolezwe - Dlamini, Sizwe Z. (Literator, 2025)
There is a dearth of research on cartoons in the African indigenous languages of South Africa. This article seeks to fill this gap by analysing isiZulu cartoons from a post-colonial point of view. The study adopts systematic visuo-textual analysis as a qualitative research technique because cartoons are the primary sources of data collection and analysis. These cartoons are composed by Mqapheli Mngadi, and they are published in the isiZulu newspaper Isolezwe. Through the application of the post-colonial theory, Barthes’ semiotic theory, and Aristotelian rhetoric theory, the findings demonstrate pertinent post-colonial issues depicted in the selected cartoons. These issues are economic, social, and political in nature. They range from issues such as gender-based violence, flux identities, difficult economic living conditions, unemployment, racism, corruption, and leadership concerns in government. These issues are depicted creatively through literal and figurative visual representation that are marked by caricature, metaphor, and personification. They are also depicted through satire as a persuasive technique, which has been determined to be effective in appealing to the audience’s logical reasoning, emotions, and character. Contribution: This article contributes to research on the decolonisation of knowledge production and representation in African media and popular culture. The article examines several perspectives on the role of visual media in shaping and expressing indigenous worldviews and experiences. Furthermore, by connecting fields such as visual communication, linguistics, rhetoric, media studies, and postcolonial theory, it opens up new avenues for critical engagement with indigenous language media while emphasising the intellectual and cultural significance of cartoon art in contemporary South African society.